Bismuth addition in Sn-Ag-Cu lead-free solder - Mohamed Ariff, Azmah Hanim; As'arry, Azizan; Abdul Aziz, Nuraini (Faculty of Engineering, Universiti Putra Malaysia, 2024)
Sn-Ag-Cu solder is a form of solder to replace Sn-Pb solder in electronic device soldering. Sn-Ag-Cu however, consists of various weaknesses when compared to traditional Sn-Pb solder in terms of mechanical properties and reliability. Alloying with elements such as bismuth, can be one of the methods to improve the solder properties. Therefore, a short review is carried out to understand the improved performance with bismuth doping in the solder melting temperature and reliability testing.